What makes people leave LESS food? Testing effects of smaller portions and information in a behavioral model. (1st August 2019) - Lorenz-Walther, Bettina A.; Langen, Nina; Göbel, Christine; Engelmann, Tobias; Bienge, Katrin; Speck, Melanie; Teitscheid, Petra
Abstract: To contribute to a better understanding of consumer food leftovers and to facilitate their reduction in out-of-home settings, our study analyzes the effects of two common intervention strategies for reducing leftovers in a holistic behavioral model. Based on a quasi-experimental baseline-intervention design, we analyzed how the display of information posters and the reduction of portion sizes take an effect on personal, social and environmental determinants in a structural equation model. Applying data from online surveys and observations among 880 guests (503 baseline, 377 intervention) during two weeks in a university canteen, the suggested model allows to assign effects from the two interventions on plate leftovers to specific changes in behavioral determinants. Portion size reductions for target dishes are found to relate to lower levels of plate waste based on conscious perception, represented in smaller portion size ratings. Effects from seeing information posters are found to base on changed personal attitudes, subjective norms and perceived behavioral control. However, depending on how an individual reacts to the information (by only making an effort to finish all food or by making an effort and additionally choosing a different dish in the canteen) there are opposite effects on these determinants and consequently also on plate leftovers. Overall, the differentiated results on intervention effects strongly support the benefits of more holistic and in-depth analyses of interventions to reduce plate leftovers and therefore to contribute to more sustainable food consumption in out-of-home settings.